With a Little Help from My Friends: The Federal Government's Reliance on Cooperation from the States in Enforcing Immigration Policy - Daniel G. Iles (Washington University Journal of Law & Policy, 2009)
Part I of this Note describes (A) the legislative developments of United States immigration policy from its roots; (B) the history of deportation laws; (C) deportation for controlled substance violations; (D) Kansas‘s modern criminal sentencing policy; and (E) the convergence of all of the above in Martinez. Part II distills (A) the trend toward exclusion in the history of immigration policy; (B) the policy considerations underlying sentencing guidelines; (C) the interplay between state and federal policymakers in immigration law; and (D) the problems with the Kansas Court of Appeals‘s decision in Martinez. Part III explores (A) the basis of the Martinez decision and the appellate court‘s misconception; (B) a hypothetical situation in which the court did not misconceive, yet made incorrect assumptions; and (C) a further hypothetical situation in which the court was correct in its assumptions, yet under any of the situations explored, its decision was inappropriate. Part IV summarizes the consequences of Martinez and the extent to which an alternative holding would promote teamwork between state and federal authorities and better execution of Congress‘s restrictive immigration policy.
Keywords: Emigration & amp; immigration; Cooperative federalism; Controlled substances; Deportation; Federal-state relations; Immigration policy; Kansas; States